EFFECT OF WORK EXPERIENCE AND EMPLOYEE COMPETENCE IN THE ADMINISTRATIVE FIELD OF EMPLOYEE PERFORMANCE IN GENERAL SECRETARIAT OF MALANG CITY - Maslikhan Firdaus, Retno (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2023)
Employee performance directly has an influence on achieving organizational goals. Therefore, there is a need for good performance management from the organization to ensure the performance of the organization through the factors of work experience and employee competence in the administrative field that employees must have so that employees can carry out their duties so that organizational goals are more easily achieved. The purpose of this study is to describe and test the work experience and employee competency in the field of administration on employee performance. This research uses a quantitative approach with multiple linear regression analysis techniques. The sampling technique used was proportional random sampling, so that a sample of 48 respondents was obtained. The results of the study show that: (1) the average work experience of employees of the General Section Malang City Regional Secretariat is for 16 years, the competence of administrative staff and employee performance is included in the good category; (2) Work experience does not affect employee performance. Competency of administrative staff has a positive and significant effect on employee performance. Work experience and competence of administrative staff simultaneously have a positive and significant effect on employee performance.